FRI0441 Neck pain in ankylosing spondylitis: focus on active inflammation at the craniocervical junction on mri. (15th June 2017) - Slobodin, G; Rosner, I; Awisat, A; Rimar, D; Shpigelman, A; Militianu, D
Abstract : Background: A wide spectrum of structural changes in the elements of craniocervical junction in patients with ankylosing spondylitis (AS) has been recently described in a retrospective study using computed tomography [1]. The clinical significance of these findings requires further elaboration. Objectives: To explore and describe inflammatory MR imaging findings in the craniocervical junction in patients with AS and neck pain. Methods: Eighteen patients with AS and continuing neck pain, as well as 9 patients with fibromyalgia of the same age and similar level of severity of neck pain, who served as a control group, underwent relevant rheumatologic examination, X-ray of cervical spine and MRI study, which included STIR, CUBE T2, FSE and FSE FAT SAT sequences before and after administration of gadolinium. Results: In the AS group, 12 males and 6 females diagnosed by 1984 New York criteria, of median age 40.5 years (range 31–61 years) and median disease duration of 8 (range 1–35) years, with 13 under treatment with anti-TNF agents were studied. All patients suffered from neck pain, with median VAS of 7 (range 2.5–10). Range of neck spine motion was limited in all but 3 patients. Seven of 18 patients had evidence of cervical syndesmophytes on X-ray. In addition to expected findings of syndesmophytes, active inflammatory lesions were seen in MR imaging in two of 18 patients with AS and in none with fibromyalgia (Fig. 1 ). Both AS patients with positive MRI were on anti-TNF therapy during the study and did not have syndesmophytes at the cervical spine as also by X-ray films. Conclusions: Active inflammation of both entheses and joints of the craniocervical junction was demonstrated by MRI in some patients with AS and persistent neck pain. Active lesions at the craniocervical junction should be included in the differential diagnosis of neck pain in AS. References: Slobodin G, Shpigelman A, Dawood H, Rimar D, Croitoru S, Boulman N, Rozenbaum M, Kaly L, Rosner I, Odeh M. Craniocervical junction involvement in ankylosing spondylitis. Eur Spine J. 2015 Dec;24(12):2986–90. Disclosure of Interest: None declared